The role of nt590 P21 gene polymorphism in the susceptibility to nasopharyngeal cancer - Soares, S.; Catarino, R.; Breda, E.; Medeiros, R.; Bravo, I. (Experimental Oncology, 2014)
Aim: The purpose of this study was to assess if the P21 nt590 polymorphism is associated with the susceptibility to nasopharyngeal cancer and with the age at diagnosis. Materials and Methods: We analyzed the frequency of 3’UTR P21 polymorphisms in blood samples from 102 nasopharyngeal cancer patients and 191 controls, with no known oncologic disease, using PCR–RFLP. Results: The polymorphism genotype frequencies were 93.2% (CC), 5.2% (CT) and 1.6% (TT) in the control group and 88.2% (CC), 10.8% (CT) and 1.0% (TT) in the cases group. We found no statistically significant association between the different P21 polymorphism genotypes and risk of nasopharyngeal cancer (p = 0.201). However, approximately a four-fold increased risk of undifferentiated nasopharyngeal carcinoma in early stages was observed for P21 T carriers (OR = 3.734; 95% IC 1.289–10.281; p = 0.01). Furthermore, our results indicate that the waiting time for onset of neoplasia in T carriers patients was 12.4 years earlier (56.5 years old), comparing with those carrying CC genotype (68.9 years old). Conclusions: Our findings suggest that the 3’UTR P21 polymorphism may play an important role in the pathogenesis and initiation, but not in the progression, of undifferentiated nasopharyngeal carcinoma. Moreover, the polymorphism seems to contribute to a significantly earlier age at diagnosis. Key Words: genetic polymorphisms, nasopharyngeal cancer, P21.